A lysin motif-containing protein (SpLysMD3) functions as a PRR involved in the antibacterial responses of mud crab, Scylla paramamosain. Issue 97 (February 2020) - Wang, Yue; Wang, Xue-Peng; Zhang, Bin; Li, Zhi-Min; Yang, Li-Guo; Li, Xin-Cang; Ma, Hongyu
Abstract: Lysin motif (LysM)-containing proteins function as pattern-recognition receptors in plants to recognize different N -acetylglucosamine-containing ligands, thereby triggering specific defense responses against pathogens. However, the biological functions of these proteins in animals remain unclear. In this study, we characterized a novel LysM protein, designated as Sp LysMD3, in mud crab Scylla paramamosain . The cDNA sequence of SpLysMD3 had 1058 bp with an open reading frame of 840 bp encoding a protein with 279 amino acid residues. The deduced protein contained a LysM domain and a transmembrane region. SpLysMD3 was highly expressed in gills, intestine, muscle, and hemocytes and upregulated after challenges with bacteria, suggesting that it may be involved in antibacterial defense. Binding assay showed that Sp LysMD3 possessed specific binding activities to all tested microorganisms as well as bacterial cell wall components lipopolysaccharide (LPS) and peptidoglycan (PGN), indicating that Sp LysMD3 was an important LPS- and PGN-binding protein in mud crab. Bacterial clearance assay revealed that coating bacteria with Sp LysMD3 accelerated bacterial clearance in vivo . The promotion of bacterial clearance by Sp LysMD3 was further determined by using SpLysMD3 -silenced crabs injected with S. aureus or V. parahemolyticus . Silencing SpLysMD3 dramatically suppressed the bacterial clearance. Meanwhile, knockdown of SpLysMD3 also severely impaired the expression of a specific set of antimicrobial peptides (AMPs); moreover, Sp LysMD3 overexpression can enhance the promoter activity of SpALF2 . These results suggested that SpLysMD3 affected bacterial clearance by regulating AMPs. Collectively, all the results demonstrated that Sp LysMD3 may function as a potential receptor involved in innate immunity by binding to LPS and PGN and by regulating AMPs to eliminate invading pathogen. This study provided new insights into the biological functions of LysM proteins in animals and the mechanisms underlying the antibacterial activity of crustaceans. Highlights: Sp LysMD3 was membrane-bound protein with a lysin motif. Sp LysMD3 displayed strong binding activity to PGN and LPS. Sp LysMD3 knockdown suppressed bacterial clearance in vivo and some AMPs' expression. Sp LysMD3 may act as a potential PRR involved in antibacterial immunity of mud crab.